Impact of using Infinity-Norm with Initial Radius on Performance and Complexity of SD Algorithm in MIMO systems (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2016)
In recent years, the iterative decoding techniques have played a role in improving the performance (e.g., bit error rate) and reducing the complexity of various digital communication systems. Techniques of Multiple-Input Multiple-Output (MIMO) are the main technology to enhance and achieve high-speed, high data rates, improved reliability and coverage in wireless communications. The modern wireless communications require a low complexity system for detection, since a high CPU processing involves more energy consumption and thus less flexibility in mobility terms. The sphere decoding (SD) technique proposed to solve this problem, such as an efficient algorithm. The norm-2 or l^2-norm (Euclidean metric) considered as a traditional norm that is used to achieve the tree traversal stage in SD algorithm. This work is divided into two parts; Firstly, we propose to using Infinity-Norm or l^∞-norm instead l^2-norm to decreases the hardware complexity of SD with a loss of performance is negligible, the simulation results show that the proposed l^∞-norm SD needs 14.5% to 5.9% fewer complexities than l^2-norm SD. Secondly, we are investigating the impact of choosing initial radius on the performance and complexity of SD algorithm, we can conclude from the simulation results, that gain a better performance requires increasing in the initial radius of an SD algorithm from d1 (γ =2) to d3 (γ =8), and this mean addition more complexity due to the tradeoff  between performance and complexity.      In recent years, the iterative decoding techniques have played a role in improving the performance (e.g., bit error rate) and reducing the complexity of various digital communication systems. Techniques of Multiple-Input Multiple-Output (MIMO) are the main technology to enhance and achieve high-speed, high data rates, improved reliability and coverage in wireless communications. The modern wireless communications require a low complexity system for detection, since a high CPU processing involves more energy consumption and thus less flexibility in mobility terms. The sphere decoding (SD) technique proposed to solve this problem, such as an efficient algorithm. The norm-2 or -norm (Euclidean metric) considered as a traditional norm that is used to achieve the tree traversal stage in SD algorithm. This work is divided into two parts; Firstly, we propose to using Infinity-Norm or -norm instead -norm to decreases the hardware complexity of SD with a loss of performance is negligible, the simulation results show that the proposed -norm SD needs 14.5% to 5.9% fewer complexities than -norm SD. Secondly, we are investigating the impact of choosing initial radius on the performance and complexity of SD algorithm, we can conclude from the simulation results, that gain a better performance require increasing in the initial radius of an SD algorithm from d1 ( =2) to d3 ( =8), and this mean addition more complexity due to the tradeoff  between performance and complexity.